EFL Students' Metacognitive Strategies in Learning Vocabulary - Septiani, Anissa Dwi; Nasrullah, Rahmat; Faridawati, Faridawati (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to find out the metacognitive strategies used by students to learn vocabulary. This research is quantitative descriptive. In four semesters, questionnaires were distributed to 116 students in the English Language Education Study Program at Muhammadiyah University of Kendari. From the research results it was found that overall in the planning aspect the highest percentage 41% shows that students sometimes plan before studying, the strategy they often use is to read the instructions carefully before starting the task related to vocabulary improvement. while for comprehension monitoring it was found that the highest percentage was 44%, which shows that students sometimes carry out comprehension monitoring to deepen their vocabulary. The types of strategies they often use are pausing while doing the task to check their understanding of vocabulary and asking them-self how well they understand when adding new vocabulary. For the information management strategy aspect, the overall result shows that the majority of students sometimes use this information management strategy with the highest percentage being 37%. The type of strategy they often use is focused on the meaning and importance of new vocabulary. In addition, the overall highest percentage in debugging strategy is 37%, which shows that students often use debugging strategies in learning vocabulary. The strategy they often use is to stop and reread the word when they are in doubts. Lastly, for evaluation aspect shows that students sometimes carry out evaluations in learning vocabulary, with the highest percentage is 43%, the type of strategy they often use is asking themselves about how good they are when learning new vocabulary, especially when it comes to developing vocabulary.